The Role Financial Literacy and Financial Planning to Increase Financial Resilience: Household Behaviour as Mediating Variable - Noni Setyorini; Rr Hawik Ervina Indiworo; Sutrisno Sutrisno (Media Ekonomi dan Manajemen, 2021)
This study aims to examine the effect of spatial literacy and financial planning by using household behavior as a mediator. The testing uses a mediation process using Smart PLS 3.0. Respondents were collected using an online survey using a simple random sampling technique. The number of respondents used in this study was 102 respondents. Based on the results of data processing, financial literacy on financial resilience is not supported. Meanwhile, the effect of financial literacy on financial resilience by mediating household behavior is accepted. The hypothesis of financial planning on financial resilience is not supported. However, the effect of financial planning on financial resilience with household behavior as mediation is supported. This research provides theoretical and practical contributions which will also be discussed further in this paper.